The Signaling Value of Internal Employee Coordination - CAI, WEI; CAMPBELL, DENNIS; YU, JIEHANG (Journal of Accounting Research, 2025)
ABSTRACT We examine the effect of internal employee coordination on customer trust, focusing specifically on employees’ responsiveness to each other as an important, quantifiable, and objective aspect of internal coordination. Using proprietary data from a company with exogenous assignment of employees to teams that serve individual customers, we study how inter‐employee responsiveness influences customer trust. Each customer is served via an app‐based group chat by a randomly assigned team of employees. Our data include more than 2 million group chat messages with over 16 thousand customers. We find that inter‐employee responsiveness serves as a credible signal that helps build customer trust, as evidenced by their subsequent contracting choices. The effect is more pronounced when the signal is (1) more frequent and (2) more intense. Our findings highlight the novel value of internal employee responsiveness as a credible signal that helps build trust with external stakeholders.